(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The paper presents an overview of the mobile telecommunications sector by highlighting the effect of the sector on the economy. The was followed by a discussion of the different types of contracts, with much focus on customer switching, so as to highlight that this industry is highly susceptible to customers switching service providers. The discussion then progressed to why customers switch, the costs and barriers associated with switching and what can be done to minimize such behaviour. A thorough review of relevant literature on consumer behaviour in general and customer satisfaction, customer loyalty and consumer switching behaviour in particular, as well as the antecedents of the aforementioned constructs, culminated in the development of a conceptual model for managing customer switching in the mobile telecommunications industry.